2020
DOI: 10.2147/ott.s240803
|View full text |Cite
|
Sign up to set email alerts
|

<p>Irinotecan Induces Autophagy-Dependent Apoptosis and Positively Regulates ROS-Related JNK- and P38-MAPK Pathways in Gastric Cancer Cells</p>

Abstract: Background: Irinotecan (IRI) is considered an option for second-line treatment of advanced gastric cancer; however, acquired drug resistance currently limits its clinical application. Recently, many researchers have shown that autophagy plays a crucial role in the resistance of tumor cells to chemotherapy and radiotherapy. In this study, we investigated the relationship between autophagy and antitumor activity of IRI in gastric cancer cells. Methods: We used MTT assay, flow cytometry and immunofluorescence sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 33 publications
(37 reference statements)
3
17
0
Order By: Relevance
“…Therefore, using agents that enhance ROS generation is improtant in providing chemosensitivity. Overall, studies are in agreement with antitumor activity of ROS and their capacity in regulating various molecular pathways [76][77][78][79][80]. However, there are controversies about the role of ROS in cancer cells.…”
Section: Ros Role In Cancersupporting
confidence: 69%
“…Therefore, using agents that enhance ROS generation is improtant in providing chemosensitivity. Overall, studies are in agreement with antitumor activity of ROS and their capacity in regulating various molecular pathways [76][77][78][79][80]. However, there are controversies about the role of ROS in cancer cells.…”
Section: Ros Role In Cancersupporting
confidence: 69%
“…It will produce a series of toxic and side effects on various cell membrane structures in cells, resulting in cell death (Hayes et al, 2020). Zhu et al (2020) reported that administration of 20 μmol/ L irinotecan for 24 h could significantly increase the ROS content in gastric cancer cells and result in apoptosis of gastric cancer cells FIGURE 6 | HCQ induces apoptosis in cholangiocarcinoma cells in an ROS-dependent manner. Cells were preincubated with GSH (3 mmol/L) for 2 h and then treated with HCQ for 24 h. (A) ROS levels in HuCCT-1 and CCLP-1 cells treated with HCQ (IC50) and GSH were detected by flow cytometry.…”
Section: Discussionmentioning
confidence: 99%
“…have proved that SNX-2112, the Hsp90 inhibitor, enhanced TRAIL-induced apoptosis and autophagy of cervical cancer cells through activating the ROS-regulated JNK-p53-autophagy-DR5 pathway ( 26 ); Zhu et al. indicated that irinotecan (IRI) stimulated the reactive oxygen species (ROS)-related JNK- and p38-MAPK signaling pathways to increase autophagy-dependent apoptosis and inhibit growth of gastric cancer cells ( 40 ). Therefore, the active status of the JNK/c-Jun signaling pathway was detected under CASK knockdown condition in the present study.…”
Section: Discussionmentioning
confidence: 99%